Barriers to seeking and delivery of essential health services in nine provinces of Afghanistan during the COVID-19 pandemic: community health workers’ perspective - Freshta Amiry; Narges Neyazi; Ali Mirzazadeh; Abdul Ghani Ibrahimi; Deena AlAsfoor; Jamshed Ali Tanoli (BMC Health Services Research)
Abstract Introduction Community health workers (CHWs) played a vital role in providing diverse essential health services to their communities during the pandemic. Using CHWs perspective, this study investigates barriers to seeking and delivery of essential health services in the nine Afghan communities during the COVID-19 pandemic. Method In this cross-sectional study, 107 primary health care clinics from 9 provinces were selected, in which around 45% of the total country population reside. We used the validated questionnaire “Community Needs, Perceptions and Demand, Community Assessment Tool” which was contextualized by WHO headquarters and the WHO Afghanistan office. Data was exported into Excel, cleaned, and then exported into and analyzed using STATA version 17. Result Most CHWs were men (80.9%), from rural areas (87.2%), and volunteers (58.1%). About 66.3% reported that lack of information about available services was a main barrier. Other reported barriers were a lack of transportation to health facilities (47.2%), their home were too far from health facilities (40.9%), and a perceived lack of medicines at facilities (23.6%). More than half of CHWs reported that they received some training on how COVID-19 spreads (67.2%), COVID-19 vaccine (65.4%), and how to use a mask properly while working (56.3%), while 27.2% said that they had not enough mask available to use. Conclusion Our research demonstrated that most barriers and concerns related to using critical services during a pandemic may be addressed by providing information about available services, providing transportation to facilities, and providing masks to personnel and individuals. CHWs could play critical role in managing and responding to emergencies and pandemics if the government invest on their capacity and motivation. Revision of training curriculum for CHWs and their job description to include the emergency and pandemic management at community level, and providing them monetary incentives are highly recommended.